ANALYSIS OF FACTORS INFLUENCING THE REALIZATION OF MURABAHAH FINANCING FOR MICRO AGRIBUSINESS ENTERPRISES IN THE TRADE SECTOR (CASE STUDY AT BMT AL-AKBAR, DELI SERDANG DISTRICT) - Siregar, Pardamean; Anggraini, Tuti; Inayah, Nurul (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Micro businesses have an important role in employment absorption and gross domestic product (GDP). The problem often faced by micro businesses is the difficulty of obtaining loans from banks. Sharia Microfinance Institutions (LKMS) are an alternative source of financing. Baitul Mal wat Tanwil (BMT) Al-Akbar is a sharia microfinance institution that provides micro business financing through murabahah financing. This research aims to analyze the factors that influence the realization of murabahah financing through customer characteristics. The sampling method was carried out using convenience sampling and the number of samples used was 40 people. The collected data was processed using multiple regression. The research results show that the significant factors are length of education, length of business, net business income for one month and collateral. Keywords: Agribusiness, Customer Characteristics, Realization Of Murabahah Financing, Multiple Regression, Micro Businesses